Direct-acting antiviral therapy is associated with a reduced risk of selected immune-mediated inflammatory diseases in chronic hepatitis C infection: A real-world cohort study - Yeong-Jang Lin; Chia-Chih Kuo; Chih-Cheng Lai; Hung-An Chen; Chao-Yu Chen (PLoS ONE, 2026)
Background Chronic hepatitis C virus (HCV) infection is associated with immune dysregulation and an increased risk of immune-mediated inflammatory diseases (IMIDs). While direct-acting antiviral (DAA) therapy achieves high rates of sustained virologic response, its long-term effects on the risk of IMIDs remain incompletely understood. Methods We conducted a retrospective cohort study using data from the TriNetX global research network (2015–2024) to evaluate the association between DAA therapy and the risk of IMIDs among adults with chronic HCV infection. Patients were categorized into DAA-treated and untreated cohorts. Propensity score matching (1:1) was applied to balance baseline characteristics between groups. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Sensitivity analyses, along with predefined positive and negative control outcomes, were performed to assess robustness. Subgroup analyses were conducted to assess potential effect modifiers. Results After matching, 35,266 patients were included in each cohort. DAA therapy was associated with a significantly reduced risk of several IMIDs, including rheumatoid arthritis (HR 0.83, 95% CI 0.71–0.97), autoimmune hepatitis (HR 0.55, 95% CI 0.31–0.96), and immune thrombocytopenic purpura (HR 0.64, 95% CI 0.44–0.93). These associations were consistent across multiple predefined time-at-risk windows. Subgroup analyses revealed that the protective associations were more pronounced among females and middle-aged individuals (41–64 years). Conclusions DAA therapy in patients with chronic HCV infection is associated with a reduced risk of specific IMIDs, suggesting potential systemic immunologic benefits beyond hepatic outcomes.